2016
DOI: 10.1038/srep37295
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and mucosal immune responses following oral adenoviral delivery of influenza vaccine to the human intestine by radio controlled capsule

Abstract: There are several benefits of oral immunization including the ability to elicit mucosal immune responses that may protect against pathogens that invade through a mucosal surface. Our understanding of human immune biology is hampered by the difficulty in isolating mucosal cells from humans, and the fact that animal models may or may not completely mirror human intestinal immunobiology. In this human pharmacodynamic study, a novel adenovirus vector-based platform expressing influenza hemagglutinin was explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
(36 reference statements)
2
27
0
Order By: Relevance
“…Vaccines using adenoviral vectors have targeted a wide range of some of the most challenging diseases, including HIV, influenza, rabies, botulism, dengue, SARS and Ebola [167173]. They are able to generate robust cellular and humoral immune responses.…”
Section: Oral Vaccine Strategies: Delivery Systemsmentioning
confidence: 99%
“…Vaccines using adenoviral vectors have targeted a wide range of some of the most challenging diseases, including HIV, influenza, rabies, botulism, dengue, SARS and Ebola [167173]. They are able to generate robust cellular and humoral immune responses.…”
Section: Oral Vaccine Strategies: Delivery Systemsmentioning
confidence: 99%
“…Clinical trials are under way (NCT02830932). Although a vaccine using the same platform was tested for influenza in mouse, ferrets, and in humans 48,79,80 showing promising results, up to date no preclinical studies using the RSV vaccine have been reported.…”
Section: Adenovirus Vectored Rsv Vaccinesmentioning
confidence: 99%
“…Immunophenotyping was performed on cryopreserved PBMCs as described previously (16). Data were collected on a BD LSR II cytometer using FACS DIVA software and analyzed using FlowJo software (version 10.2).…”
Section: Methodsmentioning
confidence: 99%
“…In their study, virus-specific ASCs that expressed the α4β7 integrin were used as a biomarker for mucosal immunity, since α4β7 is involved in selective B cell homing to mucosal intestinal tissues. The Vaxart vector approach has also been shown to induce IgA ASCs and α4β7-expressing B cells (16) in humans, suggesting that this vaccine platform is capable of initiating an intestinal immune response that could be especially advantageous for deterring a pathogen that infects the intestinal mucosa.…”
Section: Funding Vaxartmentioning
confidence: 99%
See 1 more Smart Citation